Eco-social sustainability assessment of manufacturing systems: an LCA-based framework - Haddad, Yousef; Atescan Yuksek, Yagmur; Jagtap, Sandeep; Jenkins, Simon; Pagone, Emanuele; Salonitis, Konstantinos (Elsevier, 2023)
In this paper, model-based sustainability assessment framework with social impact considerations is developed. The framework integrates the stochastic, nonlinear, and complex interrelationships that characterize most manufacturing systems, and incorporates their impact in the sustainability assessment module. The framework consists of three models that run successively, namely: stochastic discrete-event simulation (DES) model, environmental lifecycle assessment (LCA) and social LCA models. To test and validate the model, and to demonstrate its applicability and usefulness in industrial settings, a case study on the environmental and social impacts associated with the manufacturing of an aerospace component is carried out. Results revealed that integrating the stochastic behaviour of production systems can unveil production issues that are likely to arise at the strategic level and affect the sustainability performance, while not being instantly perceptible. Social LCA indicated that, although input data suffered from quality issues, there is a potential higher risk associated with overseas upstream supply chains. This risk can, however, be potentially mitigated through technology-based enhanced traceability and transparency of upstream supply chains, or even the localization of upstream activities, where possible.
Keywords: Life cycle assessment; LCA; dynamic LCA; discrete-event simulation; SLCA; social lifecycle assessment; aerospace manufacturing